2022
DOI: 10.1038/s41598-022-07254-9
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of bioconvective Darcy Forchhemier nanofluid flow with energy transition over a permeable vertical plate

Abstract: In biological systems, the MHD boundary layer bioconvection flow through permeable surface has several applications, including electronic gadgets, heating systems, building thermal insulation, geological systems, renewable energy, electromagnetism and nuclear waste. The bioconvection caused by the hydromagnetic flow of a special form of water-based nanoliquid including motile microorganisms and nanoparticles across a porous upright moving surface is investigated in this report. The combination of motile microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Madhukesh et al 53 considered CC double diffusion models to investigate 3D Prandtl liquid flow. Similar studies related to the proposed model can be found in refs 54 , 55 .…”
Section: Introductionsupporting
confidence: 82%
“…Madhukesh et al 53 considered CC double diffusion models to investigate 3D Prandtl liquid flow. Similar studies related to the proposed model can be found in refs 54 , 55 .…”
Section: Introductionsupporting
confidence: 82%
“…The necessary technique of parametric continuation method(PCM), apply to the systems of ODE's (9-11), along with the boundary conditions (12) are presented with the following steps [45][46][47][48] :…”
Section: Parametric Continuation Methods For Solutionmentioning
confidence: 99%
“…Ramzan et al 15 mechanically exemplified the influence of the entropic generation on the non-Newtonian liquid flow under the dipole impact through the thin needle. Algehyne et al 16 numerically evaluated the impact of the Darcy-Forchheimer on the flow of nanofluid with bioconvective conditions through a porous vertical plate. Mishra and Manoj 17 described the thermal performance of the MHD nanofluid flow with viscosity effects and magnetic field with the use of silver nanoparticles in the water base liquid toward the stretched cylinder.…”
Section: Introductionmentioning
confidence: 99%